H-shaped pulse generation with tunable leading edge from a Tm-doped mode-locked fiber laser. (24th December 2019) - He, Zhenwu; Chen, Yu; Deng, Zhixiang; Fang, Zhiqiang; Liu, Jun; Fan, Dianyuan
Abstract: A novel h-shaped pulse train with a tunable leading-edge (resembling a h-shaped pulse merging with a weak square pulse) is experimentally generated in a Tm-doped mode-locked fiber laser (MLFL) incorporating a 100 m highly nonlinear fiber. Through carefully adjusting the pump power and cavity polarization states, the leading-edge duration of the obtained h-shaped pulse can be widely tuned from zero (corresponding to the typical conventional h-shaped pulse train) to 567.8 ns (equivalent to the cavity roundtrip time). Our results can further facilitate understanding the intrinsic mechanism and characteristics of novel h-shaped pulse dynamics in MLFLs.